Comparison of locus of control for students at school of physical education and sports with regard to some variables - Ahmet Sanıoglu; Arife Altın; Mustafa Uslu (Türk Spor ve Egzersiz Dergisi)
This study deals with the comparisons of locus of control by some variables in students studying at the School of Physical Education and Sports. The scale for locus of control developed by Rotter was used herein. The research involved 150 female and 300 male participants. When compared to these students' locus of control in terms of genders and classes, it was observed that there was a statistical significant difference (P lt;0,05). However, no significant difference was found when these students' own departments were compared (P gt;0,05). As a result, it can be said that the variables such as the students' genders and grades showed a meaningful difference, suggesting that the locus of control was affected by the specified variables and these could direct the individuals towards the internal or external locus of control. Moreover, it is thought that the locus of control was not affected by this variable when the locus of control does not show any significant difference in the students' own departments.